Pengaruh Kompetensi Manejerial, Kewirusahaan, dan Integritas terhadap Efektifitas Manajemen PAUD Se-Kabupaten Indragiri Hulu Riau - Jacobs, Henny (Journal of Education Research in Administration and Management (JERAM), 2017)
The aim of the research is to describe the influence of managerial competencies, entrepreneurship and integrity on early chilhood manager of kabupaten Indragiri Hulu Propinsi Riau in 2015. Form used is quantitative research, with 91 samples of 118 population of manager of early childhood by using simple random sampling. The data collection techniques used are questionnaires. Analysis of the data using normality test, reggresion test and path analysis. The research results are: 1) Managerial Competencies has positive and significant influence on management effectiveness; 2) Entrepreneurship has positive and significant influence on management effectiveness; 3) Integrity has positive and significant influence on management effectiveness; 4) ) Managerial Competencies has positive and significant influence on Integrity; 5) Entrepreneurship has positive and significant influence on Integrity; 6) ) Managerial Competencies has positive and significant influence on entrepreneurship.